Enzymic synthesis of fatty esters by hydrophobic lipase derivatives immobilized on organic polymer beads - Basri, M.; Ampon, K.; Wan Yunus, W.M.Z.; Razak, C.N.A.; Salleh, A.B. (American Oil Chemists’ Society, 1995)
Lipase from Candida rugosa was modified with several hydrophobic modifiers before being adsorbed onto organic polymer beads. The effects of different enzyme modifiers, supports, solvents, reaction temperatures, fatty acids, and alcohols on the activity of the immobilized enzyme were investigated. The immobilized lipases were good biocatalysts for esterification reactions in organic solvents. They exhibited high activities in all solvents tested, including polar solvents. The activity seemed to depend on the type of support rather than on the modifier of the enzyme. The medium polar support, XAD7, appeared to be the best for the modified lipases. The immobilized lipase favored the medium-chain fatty acids rather than the long-chain fatty acids as acyl donors. The alcohol selectivity of the enzyme was unchanged upon immobilization. The native and immobilized lipases favored the short-chain and terpene alcohols as nucleophiles.